Arabic Learning Base On A Communicative Approach In Non-Pesantren School/ Pembelajaran Bahasa Arab Berbasis Pendekatan Komunikatif Di Madrasah Non-Pesantren - Baroroh, R. Umi; Tolinggi, Syindi Oktaviani R (Ijaz Arabi Journal of Arabic Learning, 2020)
With the increasing of Arabic language position in the world views, the aim of learning Arabic is also developed, it leads to various types of approaches in learning Arabic, one of them is the communicative approach. This study aimed to examine the Arabic learning based on a communicative approach in non-pesantren madrassas. This research used the method of literature study (library research). The results of this study were the learning of Arabic base on a communicative approach in non-pesantren madrassas can be implemented as well as in pesantren, it must pay attention to the eight interrelated learning components namely objectives, materials, methods, roles of educators and students, learning environment/activities, and learning evaluation. The role of the learning environment was important for achieving the objectives of communicative Arabic learning in non-pesantren madrassas. The school can carry out various supporting Arabic language programs outside the Arabic learning activities in the classroom. The basic program was not only intended for students, but also educators, employees, principals and even parents of students. Madrasah environment must be a supportive Arabic language.